The Use of Temporary Transvenous Pacing Catheters during Percutaneous Transluminal Coronary Angioplasty - Killeavy, Eugene S. (1990)
The use of temporary transvenous pacemakers during percutaneous transluminal coronary angioplasty (PTCA) over a 71/2-month period at our institution was studied retrospectively. During that time, 379 patients underwent PTCA with temporary prophylactic pacemakers in place; 398 patients underwent PTCA without prophylactic pacemakers. We examined factors such as the necessity for emergent pacemaker placement, frequency of pacing during angioplasty, indications for pacing, effectiveness of the type of pacemaker inserted, and complications associated with pacemaker placement. Pacing was indicated in 40 of the 379 patients with prophylactic pacemakers; in only 1 of the 398 patients without prophylactic pacemakers was emergent pacing required for hemodynamic instability. In the patients with prophylactic pacemakers, pacing was initiated during the procedure for 32 patients with transient hemodynamically insignificant bradycardia, 3 patients with sustained bradycardia or heart block, and 5 patients with acute vessel occlusion and associated hypotension or bradycardia, or other episodes of hemodynamic instability. Thus, in only 8 of the 379 patients was pacing instituted for something other than hemodynamically insignificant bradycardia, and in only 5 of the 379 patients was it initiated for hemodynamic instability. The overall incidence of pacing for hemodynamic instability was 6 of 777 (0.8%). The pacing catheters inserted (379 prophylactic and 1 emergent) include #7 Pacewedge (42%), #6 bipolar (29%), #7 Myler (18%), and #7 Zucker (11%). Pacing thresholds were tested in 300 patients. The Pacewedge balloon-tipped pacing catheters had a significantly higher (p < 0.001) pacing threshold for right ventricular capture than the other (non-balloon) pacing catheters used. Two cases of sustained ventricular dysrhythmia were attributed to placement of stiff pacing catheters. No other pacemaker-related complications occurred. From these data we conclude that although there are few complications associated with the prophylactic placement of pacing catheters for PTCA, the need for cardiac pacing for hemodynamic instability during PTCA is low. (Texas Heart Institute Journal 1990;17:37-41)